Resubmission of policies and certificate of insurance for accident to workman of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding resubmission of policies and certificate of insurance for accident to workman of BRAC University new campus project.